Ciprofloxacin and Norfloxacin Hybrid Compounds: Potential Anticancer Agents - Peter, Sijongesonke; Aderibigbe, Blessing A. (Current Topics in Medicinal Chemistry, 2024)
Background: The concept of utilizing drug repurposing/repositioning in the development of hybrid molecules is an important strategy in drug discovery. Fluoroquinolones, a class of antibiotics, have been reported to exhibit anticancer activities. Although anticancer drug development is achieving some positive outcomes, there is still a need to develop new and effective anticancer drugs. Some limitations associated with most of the available anticancer drugs are drug resistance and toxicity, poor bio-distribution, poor solubility, and lack of specificity, thereby reducing their therapeutic outcomes. Objectives: Fluoroquinolones, a known class of antibiotics, have been explored by hybridizing them with other pharmacophores and evaluating their anticancer activity in silico and in vitro. Hence, this review provides an update on new anticancer drugs containing fluoroquinolones moiety, Ciprofloxacin and Norfloxacin between 2020 and 2023, their structural relationship activity, and the future strategies to develop potent chemotherapeutic agents. Methods: Fluoroquinolones were mostly hybridized via the N-4 of the piperazine ring on position C-7 with known pharmacophores characterized, followed by biological studies to evaluate their anticancer activity. Results: The hybrid molecules displayed promising and interesting anticancer activities. Factors such as the nature of the linker, the presence of electron-withdrawing groups, nature, and position of the substituents influenced the anticancer activity of the synthesized compounds. Conclusion: The hybrids were selective towards some cancer cells. However, further in vivo studies are needed to fully understand their mode of action.
Keywords: Anticancer